2018
DOI: 10.1007/s00125-018-4582-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibre supplementation for the prevention of type 2 diabetes and improvement of glucose metabolism: the randomised controlled Optimal Fibre Trial (OptiFiT)

Abstract: Aims/hypothesis Insoluble cereal fibres have been shown in large prospective cohort studies to be highly effective in preventing type 2 diabetes, but there is a lack of interventional data. Our 2 year randomised double-blind prospective intervention study compared the effect of an insoluble oat fibre extract with that of placebo on glucose metabolism and incidence of diabetes. Methods A total of 180 participants with impaired glucose tolerance underwent a modified version of the 1 year lifestyle training progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 32 publications
3
67
0
6
Order By: Relevance
“…Notably, adverse effects of high protein intake on insulin sensitivity do not appear to apply in active people who relevantly stimulate also mTOR regulated increases in lean mass [3], which may compensate for proteinintake induced worsening of insulin resistance and is in line with the observation that in active athletes even very high protein intake does not appear to increase diabetes risk [3]. In addition, insoluble cereal fibers have been shown to alter the bile acid metabolic signature [15] and also may mechanically bind bile acids, thereby reducing cholesterol in plasma and restricting the absorption of dietary fats, which is beneficial for T2DM [8] The effectiveness of preventing T2DM by moderate alterations in lifestyle has been proven in two previous trials [referenced in [16]] and large epidemiological studies have identified insoluble cereal fibers as one of the most effective nutrient components for diabetes prevention [17]. However, relevantly increased fiber intake was not usually achieved.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Notably, adverse effects of high protein intake on insulin sensitivity do not appear to apply in active people who relevantly stimulate also mTOR regulated increases in lean mass [3], which may compensate for proteinintake induced worsening of insulin resistance and is in line with the observation that in active athletes even very high protein intake does not appear to increase diabetes risk [3]. In addition, insoluble cereal fibers have been shown to alter the bile acid metabolic signature [15] and also may mechanically bind bile acids, thereby reducing cholesterol in plasma and restricting the absorption of dietary fats, which is beneficial for T2DM [8] The effectiveness of preventing T2DM by moderate alterations in lifestyle has been proven in two previous trials [referenced in [16]] and large epidemiological studies have identified insoluble cereal fibers as one of the most effective nutrient components for diabetes prevention [17]. However, relevantly increased fiber intake was not usually achieved.…”
supporting
confidence: 64%
“…The fiber supplements were purified fiber extracts derived from oat hulls, which contained 70% cellulose, 25% hemicellulose, and 3-5% lignin, to be dissolved in 300 mL water. Two out of three of the participants in the high cereal fiber group did reach their target for fiber intake [16] and increased cereal fiber intake indeed tended to reduce the incidence of T2DM over 2 years; and showed significant improvements in HbA1c and blood glucose concentrations over 1 year in women, despite otherwise identical lifestyle interventions in the placebo group [16]. Further, weight loss was almost non-existent at the end of the study and not different between the high-fiber and placebo groups, supporting the hypothesis that the observed beneficial metabolic effects of high insoluble cereal fiber intake were not linked to weight change [16].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…There is much evidence in the literature to support an association between dietary fibre intake and insulin sensitivity [ 30 , 31 , 32 , 33 , 34 , 35 ]. Our own group published relevant evidence from an interventional trial using data from ProFiMet, the most highly-phenotyped cohort [ 36 ].…”
Section: The Benefits Of Dietary Fibrementioning
confidence: 99%
“…Regarding inflammation, several epidemiological studies have reported that a greater intake of total fibre was associated with lower level of C-reactive protein (CRP) (50) and various proinflammatory cytokines such as lower plasma levels of TNF-α receptor 2 and IL-6 (51) . Consistently, a recent randomised controlled trial conducted by Honsek et al reported a decrease in CRP level after 1 year intervention with insoluble fibre supplementation or promoting healthy diet (including among others, an increase in fibre intake) (52) . In addition, in the recent pilot study by Halnes et al (20) , when comparing participants with stable asthma to the control group, a higher consumption of soluble fibre was associated with lower levels of sputum neutrophils, macrophages and lymphocytes.…”
Section: Discussionmentioning
confidence: 60%